Role of the microbiota in ileitis of a mouse model of inflammatory bowel disease—Glutathione peroxide isoenzymes 1 and 2‐double knockout mice on a C57BL background. Issue 10 (18th August 2020) - Chu, Fong‐Fong; Esworthy, R. Steven; Shen, Binghui; Doroshow, James H.
Abstract: C57Bl6 (B6) mice devoid of glutathione peroxidases 1 and 2 (Gpx1/2‐DKO) develop ileitis after weaning. We previously showed germ‐free Gpx1/2‐DKO mice of mixed B6.129 background did not develop ileocolitis. Here, we examine the composition of the ileitis provoking microbiota in B6 Gpx1/2‐DKO mice. DNA was isolated from the ileum fecal stream and subjected to high‐throughput sequencing of the V3 and V4 regions of the 16S rRNA gene to determine the abundance of operational taxonomic units (OTUs). We analyzed the role of bacteria by comparing the microbiomes of the DKO and pathology‐free non‐DKO mice. Mice were treated with metronidazole, streptomycin, and vancomycin to alter pathology and correlate the OTU abundances with pathology levels. Principal component analysis based on Jaccard distance of abundance showed 3 distinct outcomes relative to the source Gpx1/2‐DKO microbiome. Association analyses of pathology and abundance of OTUs served to rule out 7–11 of 24 OTUs for involvement in the ileitis. Collections of OTUs were identified that appeared to be linked to ileitis in this animal model and would be classified as commensals. In Gpx1/2‐DKO mice, host oxidant generation from NOX1 and DUOX2 in response to commensals may compromise the ileum epithelial barrier, a role generally ascribed to oxidants generated from mitochondria, NOX2 and endoplasmic reticulum stress in response to presumptive pathogens in IBD. Elevated oxidant levels may contribute to epithelial cell shedding, which is strongly associated with progress toward inflammation in Gpx1/2‐DKO mice and predictive of relapse in IBD by allowing leakage of microbial components into the submucosa. Abstract : Hydrogen peroxide (H2 O2 ) and superoxide are generated by some bacterial genera and by the intestinal mucosa in response to bacteria. Gpx1/2‐double knockout mice are sensitive to intestinal H2 O2 production, which causes crypt apoptosis and anoikis leading to inflammation. We investigate the normal ileum pathology inducing microbiota and use antibiotics to narrow down potential candidates. The principal candidate, Lactobacillus, stands out while not demonstrating unambiguous domination in provoking the pathology.